1992
DOI: 10.1177/000331979204300310
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac Extension of a Calcified Ovarian Hemangioma— A Case Report

Abstract: The authors report a case of a fifty-five-year-old woman with clinical and echocardiographic diagnosis of right atrial myxoma. At fluoroscopy and phlebography a mobile calcified peduncle was appreciable originating from the left ovarian vein. This passed through the inferior cava to the right atrium where it wound round itself and extended into the right ventricle during diastole. The authors suspected the presence of a vascular leiomyoma. The tumor and its peduncle were removed by pulling through the right at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Approximately 83.5% of the patients had undergone a previous hysterectomy/myomectomy or had a coexisting uterine leiomyoma, suggesting uterine leiomyoma with vascular invasion as the origin of this lesion. A few patients were found with a normal uterus [3,[18][19][20], which may support the theory of ICLM originating from the venous smooth muscle wall itself. The interval between hysterectomy/myomectomy and the detection of ICLM varied from merely 3 months [21] to as long as more than 40 years [22,23].…”
Section: Epidemiology and Characterizationsupporting
confidence: 63%
“…Approximately 83.5% of the patients had undergone a previous hysterectomy/myomectomy or had a coexisting uterine leiomyoma, suggesting uterine leiomyoma with vascular invasion as the origin of this lesion. A few patients were found with a normal uterus [3,[18][19][20], which may support the theory of ICLM originating from the venous smooth muscle wall itself. The interval between hysterectomy/myomectomy and the detection of ICLM varied from merely 3 months [21] to as long as more than 40 years [22,23].…”
Section: Epidemiology and Characterizationsupporting
confidence: 63%
“…There have been previously reported studies involving a uterine leiomyoma or leiomyosarcoma extending into or simulating an atrial myxoma [10,11,12, 15]. Nevertheless, we were only able to identify one reported case documenting the treatment for both primary uterine cancer and an atrial myxoma [9].…”
Section: Resultsmentioning
confidence: 98%
“…There have been studies involving a uterine leiomyoma or leiomyosarcoma either mimicking an atrial myxoma [10] or infiltrating the atrium [11, 12], but there have been virtually no clinical cases in which an endometrial adenocarcinoma and an atrial myxoma were managed concurrently [9]. We report herein the history and complicated treatment of a patient affected by these two conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Scattered case reports of ovarian haemangioma (Tamburino et al, 1992), testicular tumour (Kanda et al, 1991), embrional carcinoma of the testis (Paule et al, 1991), testicular teratoma (Moon et al, 1992) and even pancreatic cancer (Ozben et al, 2007) have been reported so far.…”
Section: Othersmentioning
confidence: 99%